ATTACK TREE BASED CYBER SECURITY ANALYSIS OF NUCLEAR DIGITAL INSTRUMENTATION AND CONTROL SYSTEMS - Khand, P. A. (The Nucleus, 2020)
To maintain the cyber security, nuclear digital Instrumentation and Control (I&C) systems must be analyzed for security risks because a single security breach due to a cyber attack can cause system failure, which can have catastrophic consequences on the environment and staff of a Nuclear Power Plant (NPP). Attack trees have been widely used to analyze the cyber security of digital systems due to their ability to capture system specific as well as attacker specific details. Therefore, a methodology based on attack trees has been proposed to analyze the cyber security of the systems. The methodology has been applied for the Cyber Security Analysis (CSA) of a Bistable Processor (BP) of a Reactor Protection System (RPS). Threats have been described according to their source. Attack scenarios have been generated using the attack tree and possible counter measures according to the Security Risk Level (SRL) of each scenario have been suggested. Moreover, cyber Security Requirements (SRs) have been elicited, and suitability of the requirements has been checked.